KEANEKARAGAMAN NEPENTHES DI KECAMATAN SIPIROK - Ginting, Nurmaini (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2018)
This research aims to determine the diversity of Nepenthes species in Sipirok sub-district. Location determination research using survey method. The collection of the data is performed using the methods of exploration. Found 7 types of Nepenthes eustachya Nepenthes i.e., Nepenthes ovata, Nepenthes gracilis, Nepenthes rhombicaulis, Nepenthes reinwardtiana, Nepenthes tobaica and Nepenthes reinwardtiana natural silangan one x Nepenthes tobaica. Nepenthes found the lowlands and the Highlands. Nepenthes eustachya is found at an altitude of 1008 mdpl, where this type previously found only in lowland Sumatra.